2016
DOI: 10.1590/1807-1929/agriambi.v20n10p886-890
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of upland rice cultivars to aluminum and acidic pH

Abstract: A B S T R A C TAlthough the upland rice has been known by its moderate tolerance to aluminum, the presence of exchangeable aluminum in acidic soils may inhibit and compromise the adequate plant growth. However, there are few reports detailing modern cultivars used by Brazilian farmers with respect to their susceptibility to aluminum toxicity. This study aimed to characterize the cultivars currently used in the upland rice production with respect to their tolerance to aluminum and their growth under low pH cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
6
0
2
Order By: Relevance
“…The experiment was arranged in a 2 × 5 factorial randomized complete block design, with five replicates. The experiments included two upland rice cultivars (ANa7007, which is Al tolerant, and Maravilha, which is Al susceptible) (Freitas et al 2016) and four Si and Al treatments (control = without Si and Al; +Si = with Si and without Al; +Al = without Si and with Al; and +Si + Al = with Si and Al). The Si and Al concentrations in the solution were defined in preliminary studies.…”
Section: Methodsmentioning
confidence: 99%
“…The experiment was arranged in a 2 × 5 factorial randomized complete block design, with five replicates. The experiments included two upland rice cultivars (ANa7007, which is Al tolerant, and Maravilha, which is Al susceptible) (Freitas et al 2016) and four Si and Al treatments (control = without Si and Al; +Si = with Si and without Al; +Al = without Si and with Al; and +Si + Al = with Si and Al). The Si and Al concentrations in the solution were defined in preliminary studies.…”
Section: Methodsmentioning
confidence: 99%
“…The definition of castor bean lines as Al tolerant or susceptible via quartiles, using the method proposed by Fisher & Maurer (1978) and adapted by Guimarães et al (2006), was also established in upland rice plants, as demonstrated by Guimarães et al (2006) and Freitas et al (2016).…”
Section: Resultsmentioning
confidence: 99%
“…Per cent reduction in harvest index was highest in genotype Marin Chatpi and lowest per cent reduction was observed in the genotypes Rajamani followed by Rene Nepung Aam. According to Freitas et al, (2016) [3] , reduced number of panicles per plant, grain production, shoots dry matter and harvest index of upland rice cultivars were higher in sensitive cultivars than in tolerant cultivars when grown in soil containing higher amount of alumnium. According to our study, genotypes viz.…”
Section: Harvest Indexmentioning
confidence: 98%